The selection of the best solar panel for the photovoltaic system design by using AHP - Balo, Figen; Sagbansua, Lutfu (Elsevier Science Bv, 2016)
There has been numerous efforts by researchers worldwide cooperating to reduce the material costs of photovoltaic panels, efficient novel products and improve their energy efficiency and procreate innovative and practices based on photovoltaic system design technology. The aim of this paper is to select the best solar panel for the photovoltaic system design by using AHP (Analytical Hierarchy Process) from the multi-criteria decision making methods. Among 200W solar panel brands, the problem of selecting the best solar panel is evaluated, using fifteen electrical, three mechanicals, three economic, three customers and two environment related criteria. Used data is obtained from the solar panel companies worldwide. (C) 2016 The Authors. Published by Elsevier Ltd.
3rd International Conference on Power and Energy Systems Engineering, (CPESE) -- SEP 08-10, 2016 -- Kitakyushu, JAPAN
Keywords: AHP; Solar panel; Renewable energy; Multi-criteria decision making; Photovoltaic